D-PBICC Model: Digital Project-Based Learning for High School Students' Intercultural Competence - Neneng Misliyah; Darmawati Darmawati (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Intercultural Communicative Competence (ICC) has become crucial in the era of globalization, yet English teaching in Indonesia often separates language from its cultural context. This study aims to develop and test the validity, practicality, and effectiveness of the Digital Project-Based Learning for Intercultural Communicative Competence (D-PBICC) model for senior high school students within the context of the Independent Curriculum. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The limited trial subjects involved one eleventh grade class in an urban high school in Jakarta that independently implemented the Independent Curriculum. Data collection was carried out through a needs analysis questionnaire, expert validation sheets, ICC scales (pre-test and post-test), observation sheets, and a social media content analysis project assessment rubric. Quantitative data were analyzed using a paired-sample t-test in SPSS, while qualitative data were analyzed thematically using directed coding. The results of the study indicate that the developed D-PBICC model meets high validity criteria (88%) based on expert assessments, and is highly practical according to teacher and student responses. Implementation of the model significantly improved all five components of students' ICC (attitudes, knowledge, interpreting skills, finding skills, and critical cultural awareness). The social media content analysis procedure as a core assignment successfully transformed students from passive consumers into critical analysts capable of distinguishing diverse cultural products, practices, and perspectives. The main conclusion indicates that the D-PBICC model is effective as a pedagogical innovation relevant to the needs of the Independent Curriculum.